2015
DOI: 10.1038/srep14979
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient amplification of self-gelling polypod-like structured DNA by rolling circle amplification and enzymatic digestion

Abstract: The application of DNA as a functional material such as DNA hydrogel has attracted much attention. Despite an increasing interest, the high cost of DNA synthesis is a limiting factor for its utilization. To reduce the cost, we report here a highly efficient amplification technique for polypod-like structured DNA (polypodna) with adhesive ends that spontaneously forms DNA hydrogel. Two types of polypodna with three (tripodna) and four (tetrapodna) pods were selected, and a template oligodeoxynucleotide, contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The formation of complex, mesoscopic, condensed aggregates consisting of repeating DNA motifs generated by PCR reactions has been previously addressed, for instance, in the frame of medical applications [32][33][34][35][36]. Other studies have focused on mesoscopic crystallization phases of short, non-hybridizing DNA oligomers through either end-to-end stacking or crowding effects [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of complex, mesoscopic, condensed aggregates consisting of repeating DNA motifs generated by PCR reactions has been previously addressed, for instance, in the frame of medical applications [32][33][34][35][36]. Other studies have focused on mesoscopic crystallization phases of short, non-hybridizing DNA oligomers through either end-to-end stacking or crowding effects [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of RNA per single particle was found to be around 20 wt %, which we anticipate to be of a similar level for the DNA-Mg-PP i particles produced in this work. Others have also shown the generation of various macromolecular nucleic acid structures that are likely to be mediated through multiple ion bridges coordinated by magnesium ions and pyrophosphate [ 41 , 42 , 43 , 44 , 45 ]. Given our results and previous reports, it is appealing to think that under certain environmental conditions, the inorganic pyrophosphate and divalent ions (magnesium, calcium, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Besides dendrimers, Polypod-like nanostructure referred to another kind of branched nanoassembiles consist of structural body "trunk" together with many "legs". Investigators have reported various types of polypod-like DNA nanostructure, including polypodna (Yata et al, 2015), DNA nanocentipede. Their structural advantages are their long backbone and numerous branch structures.…”
Section: Polypod-like Dna Nanostructurementioning
confidence: 99%
“…Polypodna itself could serve as an immunostimulatory agent. Y-shaped polypodna could induce great amounts of cytokines TNF-a and IL-6 than normal native double-stranded DNA (Yata et al, 2015). Y L -DNA (ligated Y-shaped DNA) also exhibits TLR9-mediated activation of DCs and macrophages, as revealed by promoted expression of the immune-relevant molecules (Yang et al, 2019).…”
Section: Polypod-like Dna Nanostructurementioning
confidence: 99%